2006
DOI: 10.1002/jmri.20671
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurements of regional lung ventilation using helium‐3 MRI in a methacholine‐induced bronchoconstriction model

Abstract: Purpose: To demonstrate ventilation changes in an animal model of methacholine-induced bronchoconstriction using hyperpolarized (HP) helium-3 (He-3) MRI. Materials and Methods:Bronchoconstriction was induced in 11 healthy rats using an intravenous injection of methacholine. The He-3 was laser-polarized using a custom-built system. MRI studies were performed on a 2-Tesla bore magnet. Coronal dynamic ventilation images were obtained using a single inhalation of the laser-polarized He-3 gas before and after metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…This is important for capturing rapid airway bronchoconstriction/dilation responses (Ͻ1 min) associated with the MCh challenge in rodents and humans (6,7,18,19). Alternate means for capturing fast bronchoconstriction include the sliding pulmonary imaging for respiratory overview (SPIRO) technique (4,20). This technique is capable of making images with 5 ms temporal spacing over 5 sec and regional measurements of average inflation rate, filling time, and maximum volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important for capturing rapid airway bronchoconstriction/dilation responses (Ͻ1 min) associated with the MCh challenge in rodents and humans (6,7,18,19). Alternate means for capturing fast bronchoconstriction include the sliding pulmonary imaging for respiratory overview (SPIRO) technique (4,20). This technique is capable of making images with 5 ms temporal spacing over 5 sec and regional measurements of average inflation rate, filling time, and maximum volume.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps most important, the conventional technique involving multiple 3 He and air breathing cycles requires several minutes (Ϸ10 min) for a single ventilation map, which is likely too slow to capture rapid changes in ventilation associated with short-duration bronchoconstriction such as a methacholine (MCh) challenge (Ͻ1 min), similar to asthma (4,5). Previous work has been limited to measurement of pre-and postsensitization effects or postlong-term challenge in part due to the time required to measure ventilation using the conventional method.…”
mentioning
confidence: 99%
“…The velocity of HP gas in the lungs can be measured from velocity-encoded MR imaging sequences and HP gases lung inflow or outflow can be derived from dynamic ventilation image series [44]. Among other applications, these dynamic gas MRI techniques have been used in animal models for the evaluation of bronchoconstrictive drug effects [45] and in clinical studies following lung transplant in patients [46]. Chemical shift imaging has been demonstrated using HP 129Xe.…”
Section: Mr Imaging Using Hp 3he and 129xementioning
confidence: 99%
“…More recently, pO 2 imaging and oxygen depletion rate imaging was extended to small animal studies in rats and mice [52,53]. The potential of 3He MRI for assessing airways constriction has been demonstrated in methacholineinduced bronchoconstriction in rat models [45]. Using a Cine-MRI approach in which image acquisition was synchronized with the inhalation of the gas mixture (3He with oxygen and nitrogen), heterogeneously distributed airways constriction was observed, resulting in a partition of the lung between ventilated and non-ventilated regions.…”
Section: Preclinical Examinationsmentioning
confidence: 99%
“…Chen and Johnson (1) have observed heterogeneously distributed ventilation defects following methacholine challenge in rats. Mosbah et al (2) reported delayed distal lung filling following intravenous injection of methacholine in rats. Similarly, airway closures and ventilation losses were observed in mouse models of asthma, with the animals being sensitized to ovalbumin and challenged with methacholine (3,4).…”
mentioning
confidence: 99%